2018
DOI: 10.1038/s41582-018-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

CGRP as the target of new migraine therapies — successful translation from bench to clinic

Abstract: Treatment of migraine is on the cusp of a new era with the development of drugs that target the trigeminal sensory neuropeptide calcitonin gene-related peptide (CGRP) or its receptor. Several of these drugs are expected to receive approval for use in migraine headache in 2018 and 2019. CGRP-related therapies offer considerable improvements over existing drugs as they are the first to be designed specifically to act on the trigeminal pain system, they are more specific and they seem to have few or no adverse ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
737
0
23

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 736 publications
(774 citation statements)
references
References 135 publications
14
737
0
23
Order By: Relevance
“…1 The findings are from open-label treatment, which is inherently prone to bias and we are, naturally, not able to indicate response rates or advising this specific switch. 1 The findings are from open-label treatment, which is inherently prone to bias and we are, naturally, not able to indicate response rates or advising this specific switch.…”
Section: Non-responders To Treatment With Antibodies To the Cgrp-recementioning
confidence: 94%
See 1 more Smart Citation
“…1 The findings are from open-label treatment, which is inherently prone to bias and we are, naturally, not able to indicate response rates or advising this specific switch. 1 The findings are from open-label treatment, which is inherently prone to bias and we are, naturally, not able to indicate response rates or advising this specific switch.…”
Section: Non-responders To Treatment With Antibodies To the Cgrp-recementioning
confidence: 94%
“…1 The clinical trials investigating the different antibodies found little clinical differences regarding efficacy and safety between them, 2 and hence different modes of action of the different antibody classes are not widely discussed. Their pharmacological mode of action is under extensive investigation, and mainly peripheral sites of action are thought to be relevant.…”
Section: Non-responders To Treatment With Antibodies To the Cgrp-recementioning
confidence: 99%
“…This family also includes calcitonin (CT), adrenomedullin (AM), adrenomedullin 2 (AM2), and amylin. CGRP is a vasodilator, plays an important role in neurogenic inflammation, and thus has gained considerable interest for the treatment of migraine . Three antibodies against either CGRP or a CGRP receptor (erenumab, fremanezumab, and galcanezumab) have recently been approved for the treatment of migraine .…”
Section: Introductionmentioning
confidence: 99%
“…Oral salicylate administered during migraine attacks resulted in lower serum drug levels, compared to administration either between attacks 15 or during attacks pretreated with prokinetic agents (eg, metoclopramide), though this study was limited by failure to use subjects as their own controls. 24 In some 25,26 but not all 27 human studies, CGRP is elevated in jugular venous blood. [17][18][19] Slower rates of gastric emptying have also been correlated with greater headache severity in migraine.…”
Section: Introductionmentioning
confidence: 99%